Respiratory Changes under Spinal Anaesthesia for Laparoscopic Gynaecological Procedures- a comparison with General Anaesthesia - Masum, Abdullah; Kalam, Farzana; Alam, Md Mahbub Ul (Journal of the Bangladesh Society of Anaesthesiologists, 2021)
Background: Laparoscopic surgery has become a frequently applied technique for a wide field ofindications. The procedure has become the gold standard for many procedures, with some of the mostcommon being gynecological procedures and appendectomy. Laparoscopic procedures that are widelyused in gynecological surgery are commonly applied under general anesthesia (GA). Now a days spinalanaesthesia (SAB) has become a routine technique for healthy patients. It is currently presumed thatspinal anaesthesia can compromise respiratory muscle function during carbon dioxide (CO2)pneumoperitoneum and causes some respiratory changes. Objective: This study was designed to compare the respiratory effects of CO2 pneumoperitoneumunder spinal anaesthesia with general anaesthesia for short duration (<1hr) laparoscopicgynaecological procedures. Methods: A total number of sixty female patients, thirty in each group of ASA grade I & II wereenrolled for the study. Group I patients received lumber SAB with 15 mg heavy bupivacaine and 25mcg fentanyl. Group II patients received standard general anaesthesia with propofol, halothane andfentanyl. Baseline heart rate, blood pressure, respiratory rate, ETCO2 & SPO2 were noted in allpatients. Arterial blood gas analysis was done at time 0, 20 and 40 min after initiation ofpneumoperitoneum. Continuous ECG, pulse oximetry, noninvasive blood pressure, and ETCO2 weremonitored during the procedure. Any per operative and post-operative side effects were recorded andmanaged. Results: There were no observed changes in the respiratory rate. In group I, ETCO2 increased in astepwise manner over the first 10 min and reached a plateau between 15th and 30th min and declinedafter deflation of pneumoperitoneum. Arterial CO2 tension also increased at 20 min with significantchanges (p=0.000) in arterial to end tidal carbon dioxide tension. ETCO2 and arterial carbon dioxidetension changes were almost similar in both groups. Conclusion: Arterial and end-tidal CO2 tension changes during lower abdominal laparoscopicsurgery under SAB remain within physiological limits and comparable to the CO2 tension under GA.SAB may be adopted in ASA physical status I and II patients with proper preoperative counseling.Hence it is a safe alternative to GA with minimum respiratory alterations. JBSA 2021; 34 (2) : 10-15